2021
DOI: 10.1089/nat.2021.0055
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli RNase H Discrimination of DNA Phosphorothioate Stereoisomers

Abstract: Phosphorothioate (PS) modification of antisense oligonucleotides (ASOs) is a critical factor enabling their therapeutic use. Standard chemical synthesis incorporates this group in a stereorandom manner; however, significant effort was made over the years to establish and characterize the impact of chiral control. In this work, we present our in-depth characterization of interactions between Escherichia coli RNase H and RNA-DNA heteroduplexes carrying chirally defined PS groups. First, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, single R p walk and SSR walk in the DNA gap region were conducted to find the stereoisomers showing the best activity. Similar strategies have been reported for the identification of the optimal stereochemistry (42, 43). After evaluating the activity of all the synthesized stereoisomers, it was found that R p at specific positions (e.g., at G7-A8 for ASO-409 (Figure 5) and at G8-A9 for ASO-486 (Figure 6)) is crucial to have good knockdown activity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, single R p walk and SSR walk in the DNA gap region were conducted to find the stereoisomers showing the best activity. Similar strategies have been reported for the identification of the optimal stereochemistry (42, 43). After evaluating the activity of all the synthesized stereoisomers, it was found that R p at specific positions (e.g., at G7-A8 for ASO-409 (Figure 5) and at G8-A9 for ASO-486 (Figure 6)) is crucial to have good knockdown activity.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, the presence of a second R p linkage did not give significant activity gain (e.g., ASO-409-SSR2-M vs. ASO-409-R3-M, and ASO-486-SSR2-M vs. ASO-486-R5-M). It is reported that the position of R p linkage in the gap region guides the RNase H cleavage site and selection of the position of R p linkage reinforcing the cleavage at the native cleavage sites gives a cleaner cleavage profile and higher knockdown activity (42, 43). The RNase H cleavage site analysis showed that ASO-486-SSR2-R and ASO-486-R5-R result in an increased cleavage at the same cleavage site presumably due to the R p linkage at G8-A9 (Supplementary Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for about 50 years now that this modification makes the oligonucleotides resistant to nuclease degradation, likely because of the larger van der Waals radius of the sulfur atom displacing the metal ions at the active sites of nucleases [ 19 , 20 , 21 ]. Furthermore, PS-modified ASOs enable the cleavage of the hybridized RNA strand by RNase H [ 22 , 23 ]. As the ASO is still active following target degradation, this mechanism dramatically enhances its inhibitory activity.…”
Section: Evolution Of the Chemistries And Pharmaceutical Properties O...mentioning
confidence: 99%
“…The replacement of phosphodiester (PO) with phosphorothioate (PS) linkages was the first chemical modification to be investigated and it is still the most extensively used, in particular, in RNase H-dependent ASOs [ 1 , 4 , 6 , 7 ]. In these ASOs, replacement of the PO with PS improves resistance to nucleases and facilitates cellular uptake and bioavailability in vivo without significantly impairing hybridization with the target RNA or the posthybridization RNase H activation [ 1 , 4 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%